Gangrenous cholecystitis as an incidental finding during emergency laparotomies for acute abdomen at a tertiary centre: a case series - Gopal, Vaibhav Raj; Rai, Priyanka; Singh, Sunil Kumar; Singh, Amarjot; Bhargav, Mithlesh; Gulfran, M. (International Journal of Research in Medical Sciences, 2024)
Gangrenous cholecystitis is an uncommon cause of acute abdomen in surgery emergency. Most of the times, diagnosis is settled intraoperatively as signs and symptoms are non-specific. CT scan of abdomen can help in making a diagnosis but should be done only if the patient is stable. Here we have reported three cases in which laparotomy was done in view of acute abdomen with signs of peritonitis and gangrenous cholecystitis was found as an incidental finding. One patient had spontaneous gangrenous cholecystitis with gall bladder perforation with biliary peritonitis. The second patient had gangrenous gall bladder perforation secondary to gall bladder malignancy and the third patient had spontaneous gangrenous cholecystitis with terminal ileal stricture presenting as acute intestinal obstruction. A decision to perform cholecystectomy in such cases depends on the feasibility, general condition of the patient and the cause of gall bladder perforation.